Pendidikan Kisah Islami pada Anak - Jannah, Kunny Khulatal; Mawardi, Kholid (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
In the holy book of Al-Quran there are many stories that can be taken from valuable ibroh (lessons) for students. The story of prophethood, the story of pious people, the story of the people affected by the punishment, and so on. In addition to being interesting, the Quranic story method opens insight into thinking, a high sense of curiosity about past events that can be used as a foothold in treading life in the future. This Quranic story method also has its own impression because it is easier to remember and absorb well if the educator is able to convey it according to the appropriate principles, strategies and steps. Educators can develop principles, strategies and steps in the storytelling according to their own ideas and creativity. The authenticity of the Quranic story which is unquestionably true can add to the scientific treasures, nourish faith, and motivate listeners, especially students. The Quranic story method will not be obsolete by the times and technological advances until humans are still willing to listen, willing to learn and change themselves